Climate Change, Migration and Voice: An Explanation for the Immobility Paradox - Michel Beine; Ilan Noy; Christopher Parsons (Center for Economic Studies and ifo Institute (CESifo), 2019)
This paper sheds light on the apparent paradox, wherein populations adversely affected by climatic conditions fail to migrate as much as would otherwise be expected. Drawing on Hirschman's treatise on Exit, Voice and Loyalty, we develop a simple model, which highlights the theoretical case for a substitution effect between voicing and emigration. We subsequently provide causal evidence of voicing representing a new mechanism through which countries adapt to climate change, implementing wage differentials and changes in visa policies at destination as instruments. More intense voicing, as captured by greater numbers of press reports, is associated with lower emigration rates. This substitution effect holds for both internal and international voicing. Our results suggest that restrictions on mobility could result in increasing voicing, both within and between countries.
Keywords: F22; O15; P16; O57; 330; emigration; climate change; voicing; trapped populations